Gang Activity and Overall Levels of Crime: A New Mapping Tool for Defining Areas of Gang Activity Using Police Records - Block, Richard (Journal of quantitative criminology, 2000)
In this note, a new method for defining gang activity areas based uponpolice records is illustrated using the Chicago Police Department's1996 incident files. This method is based upon standard geographictechniques and uses a uniform grid that divides the city into 150-msquares. It is shown that this technique may be useful both in describinggang activity areas and in describing the spatial distribution of crime inlarge cities. A strong relationship is found between the number of gangsthat are active in an area and the general level of criminal activity.